Deterring cyber warfare bolstering strategic stability in cyberspace - Mazanec, Brian M.; Thayer, Bradley A. (Palgrave pivot, 2015)
This timely study reflects increased international interest in cyber warfare, and is based on the recognition that information networks in cyberspace are becoming operational centres of gravity in armed conflict.